2008
DOI: 10.1039/b808471h
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrolysis of cellulose into glucose over solid acid catalysts

Abstract: The mildly hydrothermal method using solid acid catalysts for the glucose production from cellulose can be one of the key technologies for a future sustainable society using cellulose biomass. This article is the first to indicate solid acid catalysis for the hydrolysis of cellulose with b-1,4-glycosidic bonds into glucose selectively higher than 90 C-%. Among the solid acid catalysts we tested, such as the H-form zeolite catalysts and the sulfated and sulfonated catalysts, a sulfonated activated-carbon cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
388
2
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(405 citation statements)
references
References 23 publications
8
388
2
7
Order By: Relevance
“…Amorphous carbon bearing SO 3 H, COOH, and OH groups as catalyst gave 10% glucose yield at 373 K after 3 hr [10,29]. But, using the same type of catalyst, Onada obtained 40.5% yield of glucose at 423K in 24h [30]. Biobased catalysts in combination with silica or other supports have been able to break down cellulose.…”
Section: Ii-biobased Catalyst From Based Biobased Catalyst As Catalysmentioning
confidence: 99%
“…Amorphous carbon bearing SO 3 H, COOH, and OH groups as catalyst gave 10% glucose yield at 373 K after 3 hr [10,29]. But, using the same type of catalyst, Onada obtained 40.5% yield of glucose at 423K in 24h [30]. Biobased catalysts in combination with silica or other supports have been able to break down cellulose.…”
Section: Ii-biobased Catalyst From Based Biobased Catalyst As Catalysmentioning
confidence: 99%
“…Traditionally, catalytic systems based on enzymes, dilute acids, and supercritical water are employed in the above process; however, these have significant disadvantages such as high costs, corrosion hazard, low reaction rates, and difficulties in the separation of products and catalysts. To overcome these problems, the use of heterogeneous catalysts in this process has attracted a great deal of interest due to the large potential, both in terms of their activity and selectivity and the possibility of developing a clean technology (Huber et al, 2006;Luo et al, 2007;Onda et al, 2008;Komanoya et al, 2011). Noble metal-based catalysts have been extensively studied in the cellulose conversion reactions and frequently exhibit high activity.…”
Section: Introductionmentioning
confidence: 99%
“…[22] It has been suggested that the quantum confinement effects change the electronic structure of this noble metal and lead to the unusual catalytic activities observed. [23,24] This discovery has spurred extensive research efforts in searching novel nanocatalysts for the important catalytic reactions with low reactivity, such as activation of saturated hydrocarbons in reforming reactions [25,26], oxygen reduction reactions in fuel cells [27], and lingo-cellulose biomass hydrolysis [28][29][30][31][32]. For example, it has been reported that small, charged metal clusters exhibit facile activation and dehydrogenation of methane molecules.…”
Section: Highly-active Nanocatalystsmentioning
confidence: 99%